Śląsk i Czechy oczami magnata litewskiego. Osiemnastowieczny diariusz podróży starosty wiłkomierskiego Benedykta Tyzenhauza - Ziober, Aleksandra (In Gremium. Studies in History, Culture and Politics, 2015)
Silesia and the Czech Republic through the eyes of Lithuanian magnate. Eighteenth-century travel diary of starost of Wilkomierz Benedict Tyzenhauz Travels through Europe among the nobility and magnates of the Crown and the Grand Duchy of Lithuania experienced its heyday in the seventeenth and eighteenth centuries. They had a various character: educational, therapeutic, or diplomatic. Many Lithuanian magnates by virtue of its financial resources decided on a long expeditions through the old continent and left after them travel reports rich in interesting descriptions of the surrounding reality. Such an example may be unknown until now the memories of the peregrination through Silesia of starost of Wilkomierz Benedict Tyzenhauz. He set out on his journey in the mid-eighteenth century, and came to Wroclaw, about which left an interesting description on the pages of his memories. From the capital of Lower Silesia he went towards Prague, along the way describing the encountered village, which he visited. Particular interest of magnate aroused churches, palaces and gardens. His relationship of the journey ends with the description of Prague where, most likely, magnate returned to the grounds of the Grand Duchy of Lithuania